Optimizing Indoor Microclimate and Thermal Comfort Through Sorptive Active Elements: Stabilizing Humidity for Healthier Living Spaces - Peterková, Jitka; Zach, Jiří; Novák, Vítězslav; Korjenic, Azra; Sulejmanovski, Abdulah; Sesto, Eldira (MDPI, 2024)
This paper investigates the potential use of natural materials and elements for stabilizing indoor humidity levels, focusing on creating healthier living environments in buildings. Unstable indoor microclimates, particularly extreme humidity levels, can negatively affect human health by causing issues such as condensation, mold growth, or dry mucous membranes. In this work, we explore how sorptive materials can maintain indoor humidity within the optimal range of 40-50%. The aim is to identify optimal solutions for moisture control using passive elements, such as unfired ceramic components, which demonstrate high sorption activity within the 35-55% relative humidity range. These elements can effectively absorb moisture from, or release it back into, the indoor environment as needed. Five clay types based on different clay minerals were analyzed in the research in order to assess how their structures influence moisture adsorption behavior. These elements can be combined with green/active elements and standard measures, such as ventilation or targeted room air exchange, to improve indoor humidity regulation. The evaluation of the results so far indicates that the use of clay-based elements in the interior offers a sustainable and natural approach to maintaining optimal indoor microclimate conditions. The slab elements from all 5 clay formulations investigated effectively support indoor humidity stabilization.

This paper investigates the potential use of natural materials and elements for stabilizing indoor humidity levels, focusing on creating healthier living environments in buildings. Unstable indoor microclimates, particularly extreme humidity levels, can negatively affect human health by causing issues such as condensation, mold growth, or dry mucous membranes. In this work, we explore how sorptive materials can maintain indoor humidity within the optimal range of 40-50%. The aim is to identify optimal solutions for moisture control using passive elements, such as unfired ceramic components, which demonstrate high sorption activity within the 35-55% relative humidity range. These elements can effectively absorb moisture from, or release it back into, the indoor environment as needed. Five clay types based on different clay minerals were analyzed in the research in order to assess how their structures influence moisture adsorption behavior. These elements can be combined with green/active elements and standard measures, such as ventilation or targeted room air exchange, to improve indoor humidity regulation. The evaluation of the results so far indicates that the use of clay-based elements in the interior offers a sustainable and natural approach to maintaining optimal indoor microclimate conditions. The slab elements from all 5 clay formulations investigated effectively support indoor humidity stabilization.
Optimizing Indoor Microclimate and Thermal Comfort Through Sorptive Active Elements: Stabilizing Humidity for Healthier Living Spaces
Keywords: non-fired ceramic; clay minerals; microclimate; sorption/desorption of moisture; moisture buffering capacity; internal environment of buildings; non-fired ceramic; clay minerals; microclimate; sorption/desorption of moisture; moisture buffering capacity; internal environment of buildings